Expanding the cross-cultural psychological assessment tool box with IQ test short forms. Issue 1 (2nd January 2022) - Nuñez, Alicia; San Miguel, Liza; Gomez-Batista, Saily; Etcoff, Lewis; Barchard, Kimberly A.; Donohue, Bradley; Allen, Daniel N.
Abstract: Objective: Short forms of standard intelligence tests are useful in clinical and research settings where administration of a full intelligence test is impractical or unnecessary. In cross cultural contexts where few tests are available, including brief intelligence tests, short forms may be particularly useful to meet clinical and research needs. However, there is little cross-cultural research on the validity of short forms. This study evaluated feasibility of short form development for the Spanish version of the Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV) and examined comparability of short-form IQ estimates in Spanish- and English-speaking children with Attention-Deficit/Hyperactivity Disorder (ADHD). Method: Participants included children with ADHD who were administered the WISC-IV Spanish ( n  = 165) or WISC-IV ( n  = 299). Full Scale IQs (FSIQs) were calculated for two-, three-, four-, and five-subtest short forms. Misclassification rates, mean absolute differences, and intraclass correlation coefficients (ICCs) were used to determine short form accuracy in estimating FSIQ. Results: The WISC-IV short forms examined had generally strong psychometric properties (e.g., ICCs ranged from .78 to .94) and level of accuracy in estimating FSIQ did not differ across primary language of Spanish or English. Conclusions: Findings support feasibility of IQ short form development to help address mental health disparities in research and clinical screening for Spanish- and English-speaking pediatric populations with ADHD.